Return to Stronger Employment Growth Expected in Cities - Anja Rossen (Wirtschaftsdienst)
Abstract This paper presents a new facet of the regional forecasts of the Institute for Employment Research (IAB). For the development in 2022, we report results at the level of administrative district types of the Federal Institute for Research on Building, Urban Affairs and Spatial Development (BBSR). Overall, the forecasts for 2022 suggest a return to the regional disparities that already existed before the pandemic with regard to the development of unemployment and employment. While there are no major differences between the administrative district types in the unemployment forecast, the expected growth in employment increases in cities and urban areas compared to the previous year, but stagnates in the case of the two rural structural types.